Peripheral CB1R as a modulator of metabolic inflammation - Han, Ji Hye; Kim, Wook (FASEB Journal, 2021)
Obesity is associated with chronic inflammation in insulin-sensitive tissues, including liver and adipose tissue, and causes hormonal/metabolic complications, such as insulin resistance. There is growing evidence that peripheral cannabinoid-type 1 receptor (CB1R) is a crucial participant in obesity-induced pro-inflammatory responses in insulin-target tissues, and its selective targeting could be a novel therapeutic strategy to break the link between insulin resistance and metabolic inflammation. In this review, we introduce the role of peripheral CB1R in metabolic inflammation and as a mediator of hormonal/metabolic complications that underlie metabolic syndrome, including fatty liver, insulin resistance, and dyslipidemia. We also discuss the therapeutic potential of second- and third-generation peripherally restricted CB1R antagonists for treating obesity-induced metabolic inflammation without eliciting central CB1R-mediated neurobehavioral effects, predictive of neuropsychiatric side effects, in humans.
Keywords: Gene Expression Regulation; Humans; Inflammation; Obesity; Receptor, Cannabinoid, CB1; cannabinoid 1 receptor; endocannabinoid; inflammation; macrophage; metabolic disorder